REKONSTRUKSI EPISTEMOLOGI ISLAM BERKEMAJUAN MUHAMMADIYAH DALAM MERESPON DISRUPSI DIGITAL: INTEGRASI MANHAJ TARJIH, PENDIDIKAN PROGRESIF, DAN TRANSFORMASI SOSIAL - Ismegawati; Kailani; Devi; Heri (Educational Research Center, 2026)
The rapid expansion of digital technologies has fundamentally transformed the production, dissemination, and validation of knowledge, creating new epistemic challenges for Muslim societies. The emergence of artificial intelligence, algorithmic information systems, and digital religious authorities has disrupted conventional structures of knowledge and weakened the boundaries between religious authority, scientific rationality, and public discourse. This study aims to reconstruct the epistemological framework of Muhammadiyah’s Progressive Islam (Islam Berkemajuan) as a response to digital disruption through the integration of Manhaj Tarjih, progressive Islamic education, and social transformation. Employing a qualitative library research design combined with critical conceptual analysis, the study examines Muhammadiyah’s primary doctrinal documents, including Risalah Islam Berkemajuan, Himpunan Putusan Tarjih, Pedoman Hidup Islami Warga Muhammadiyah, and relevant scholarly literature on Islamic epistemology, digital religion, and technological transformation. The findings reveal that Progressive Islam functions as an epistemological paradigm that integrates revelation, rational inquiry, empirical knowledge, and social praxis within a coherent framework of tajdid (renewal), tanwir (enlightenment), and human welfare. Furthermore, the reconstruction of Manhaj Tarjih demonstrates a methodological shift toward the integration of bayani, burhani, and maqasidi approaches, enabling Islamic knowledge to engage constructively with contemporary digital challenges. The study also highlights the strategic role of progressive Islamic education in cultivating critical digital literacy and ethical awareness, while digital social transformation strengthens societal resilience and public benefit. These findings culminate in the formulation of the Progressive Islamic Epistemology Model (PIEM), which offers an integrative framework for harmonizing revelation, scientific reasoning, technological development, and social welfare in the digital age. The study contributes to contemporary discussions on Islamic epistemology by positioning digital disruption as an opportunity for epistemological renewal rather than merely a technological challenge.